<u><em>Answer:</em></u>
(m×1/3)-6=y
<u><em>Step-by-step explanation:</em></u>
- Start with m as the unknown variable.
- Now multiple that by 1/3 to find that portion of m. (m×1/3)
- Lastly, subtract 6 and set the expression equal to y. (-6=y)
- Thus we get our final equation: (m×1/3)-6=y
Answer:
In this case, the factor that comes out is x=−3, so you would divide by (x+3). Repeat until you've reduced to a quadratic, and then use the quadratic formula to find the irrational coefficients (if any). Simple factorisation solves your problem. Hence the 4 roots are x=12,x=−3,x=2i and x=−2i.
5/6
Step-by-step explanation:
Step-by-step explanation:
You mean the answer is - 14
So - 14 + (-4) =
- 14 - 4 = 18
Answer:
9 tables
Step-by-step explanation:
All we have to do is see how many time 6³/₄ ft. can fit in 60³/₄ ft. through division.
60 ³/₄ ÷ 6 ³/₄ =
²⁴³/₄ ÷ ²⁷/₄ =
²⁴³/₄ × ⁴/₂₇ =
²⁴³/₂₇ =
9 tables